Production of different mushroom protein hydrolysates as potential flavourings in chicken soup using stem bromelain hydrolysis - Ang, San-San (Array, 2019)
The pleasant taste of edible mushrooms, which is attributed to their high protein content, makes them an attractive source for the production of protein hydrolysates with good taste properties. In the present work, different mushroom protein hydrolysates were produced from shiitake, oyster, bunashimeji and enoki mushrooms using stem bromelain hydrolysis at 0.5 % (m/m) enzyme/substrate ratio at pH=6.5 and 40 °C for 20 h. The produced liquid mushroom protein hydrolysate yielded 0.77–0.92 % crude protein (p>0.05). Bunashimeji mushroom protein hydrolysate was the lightest in colour, while shiitake mushroom protein hydrolysate was the darkest (p0.05), with the highest yield of bunashimeji and the lowest of shiitake mushroom protein hydrolysate.